Does tax enforcement reduce corporate environmental investment? evidence from a quasi-natural experiment - He, Lu; Xu, Lin; Duan, Kaifeng; Rao, Yulei; Zheng, Chuanzhen (Frontiers in Environmental Science, 2024)
The transition to a green, sustainable economy is largely reliant on corporate investment in the realm of environmental protection. Utilizing the adoption of the third phase of the Golden Tax Project (GTPIII) as a quasi-natural experiment, this paper examines how corporate environmental investment changes in response to greater tax enforcement. Our results reveal that tougher tax enforcement significantly lowers corporate environmental investment. Such an effect is stronger for firms faced by high financial constraints and those operating in non-heavy-polluting industries. Moreover, the mechanism analysis indicates that the higher tax burden induced by greater tax enforcement is the potential channel. Overall, this paper shows that stricter tax enforcement could potentially result in adverse spillover effects on corporate environmental investment, which warrants attention in tax collection practices.